A Video-Based Behavioral Intervention Associated with Improved HPV Knowledge and Intention to Vaccinate - Sarah Marshall; Anne C. Moore; Aoife Fleming; Laura J. Sahm (Vaccines, 2022)
The aim of this study was to design, develop, and evaluate the feasibility of a theory- and evidence-based intervention to improve human papillomavirus (HPV) and HPV vaccine knowledge and intention to vaccinate, among parent–daughter dyads. A theory- and evidence-based online behavioral intervention, “Is the HPV vaccine for me?”, was developed to improve HPV and HPV vaccine knowledge and intention to vaccinate. Knowledge, intention to vaccinate, and feasibility of the intervention were evaluated in a prospective, randomized, controlled feasibility trial. A total of 49 parent–daughter dyads completed the baseline knowledge assessment (n = 24 control, n = 25 intervention), and 35 dyads completed the knowledge assessment at week 2 (n = 17 control, n = 18 intervention). The intervention resulted in a statistically significant increase in HPV and HPV vaccine knowledge and intention to vaccinate. All intervention participants found the video interesting, while 96% found it useful. This intervention was found to be useful, effective, safe, and acceptable in this feasibility study.